Phase transition and structures of the twinned low-temperature phases of (Et(4)N)[ReS(4)] - Bernhardt, Eduard (Acta Crystallogr C Struct Chem, 2020)
The title compound, tetraethylammonium tetrathiorhenate, [(C(2)H(5))(4)N][ReS(4)], has, at room temperature, a disordered structure in the space group P6(3) mc (Z = 2, α-phase). A phase transition to the monoclinic space group P2(1) (Z = 2, γ-phase) at 285 K leads to a pseudo-merohedral twin. The high deviation from the hexagonal metric causes split reflections. However, the different orientations could not be separated, but were integrated using a large integration box. Rapid cooling to 110–170 K produces a metastable β-phase (P6(3), Z = 18) in addition to the γ-phase. All crystals of the β-phase are contaminated with the γ-phase. Additionally, the crystals of the β-phase are merohedrally twinned. In contrast to the α-phase, the β- and γ-phases do not show disorder.